Compartmentalized vs. non-compartmentalized translocations in metal porphyrin complexes. (26th January 2016) - Le Gac, Stéphane; Boitrel, Bernard
Abstract : Strapped porphyrin ligands exhibit instantaneous and easy-to-control formation of various bimetallic species featuring new coordination modes and dynamics. Abstract : Double translocation processes in homo- and heterobimetallic bis-strap porphyrin complexes rely on the coexistence of two different coordination modes namely out-of-plane (OOP, bound to the N-core) and hanging-atop (HAT, bound to the strap). Two different dynamics were encountered: (i) the metal ions stay on their respective side of the macrocycle while exchanging between the strap and N-core binding sites (compartmentalized process); (ii) the metal ions exchange between the two sides of the porphyrin and maintain their OOP/HAT coordination modes (non-compartmentalized process). Various stimuli were used to tune these dynamic bimetallic systems (allosteric effector, acid–base conditions, dynamic constitutional evolution, light exposure).